Extended of Diagnostic Capabilities for the Rhinomanometry Method - Аврунін, О. Г.; Avrunin, O. G.; Shushlyapina, N. O.; Ivanchenko, J. (Publishing House WSZiA, 2015)
Extended of diagnostic capabilities for the Rhinomanometry method are described in this paper. The theoretical base and possibilities of computer rhinomanometry for functional diagnostic of nasal breasting are proposed. The developed method of dynamic posterior rhinomanometry allows to determine the value of the aerodynamic resistance of physiological nasal breathing in rest and in forced mode, which is especially important to determine the maximum air conduction of the nasal cavity. The estimation of phase difference about 9° between the signals of the air flow and pressure in the nasal cavity is calculated. A method for evaluating the functional state of the nasal valve, which allows by waveform analysis of air flow are proposed. The definition of statistical significance of the above parameters in the diagnosis of respiratory diseases require further research and medical studies.
Keywords: Functional Diagnostic; Rhinomanometry; Evidence Based Medicine; Pressure; Airflow; Nasal Resistance; Nasal Airways